The Effects of Users Participation on the Internal Control Systems on Performance of Projects in Local Government Authorities in Tanzania - Amani Mbogella (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2022)
There are differing viewpoints upon the participation of users of internal control system towards the development of internal control systems of the projects. One argument suggest that users of internal control systems should not be involved upon development of internal control systems since are implementers of the system. A counter argument is that if users of the internal controls are involved into development of internal control systems may easily violate the internal controls for their own benefits. The objective of the study mainly is to determine the relationship of internal control systems and project performance by employing the participation of users of the internal control systems. This study adopted a cross sectional research design, where analysis constituted data of variables which were collected at one given point of time across a sampled population. The population consisted of 1,002 employees of the selected Councils (Ilala, Dodoma, Iringa, Singida and Chamwino Councils) who are responsible for projects implementation. Sample of 278 staff has been selected from the population of 1,002 based on statistical formula. Primary and secondary data were collected where by structured questionnaires, focused group discussion and interview methods were employed under the study. The overall results, indicate that on average score (2.6710) of respondents disagreed that users of internal control systems (ICSs) are participated on the development of internal control systems.Participation of users statistically significance (p-value<0.01) and had positive influence on performance of project. This implies that a unit change in Participation users will increase project performance by the rate of 0.221. The studyalso indicates that, users of internal control systems should fully be involved into development of the systems so as the systems to be effective. Once the system is effective the study shows that there is positive relationship between the effectiveness of internal control systems and the performance of the projects. In additional the result shows that users of the internal control systems are inadequately involved upon development of internal control systems, as a result the internal controls are weak and finally led to failure of the projects in local government authorities in Tanzania context.